Balance rehabilitation and Long Covid syndrome: effectiveness of thermal water treatment vs. home-based program - Maccarone, Maria Chiara; Contessa, Paola; Passarotto, Edoardo; Regazzo, Gianluca; Masiero, Stefano (Frontiers in Rehabilitation Sciences, 2025)
IntroductionBalance concerns are increasingly recognized as a common presentation in patients with Long Covid. This study investigates the effects of two distinct rehabilitation programs on balance in a cohort of sixty participants experiencing medium-to-long-term symptoms following SARS-CoV-2 infection.MethodsIndividuals were enrolled and randomly assigned to either a spa resort rehabilitation program or a supervised home-based rehabilitation program. The study assessed balance and proprioception by analyzing the center of pressure trajectory during a standing task performed with eyes open and closed before, after, and at a 3- and 6-month follow-up after the rehabilitation program.ResultsResults indicated that, right after rehabilitation, participants who enrolled in the home-based program demonstrated more significant improvements in mean stay time and in the standard deviation of oscillations in the antero-posterior direction than those who enrolled in a spa-resort program. On the other hand, at the 3-month follow-up, individuals who enrolled in the spa-resort program exhibited improvements in the standard deviation of oscillations in the antero-posterior direction, indicating ongoing benefits over time.DiscussionThese findings suggest that appropriate rehabilitation programs, whether at home or in spa resorts, can contribute to enhancing overall physical function in these patients.